Nonpharmacological Correction of Hypersympatheticotonia in Patients with Chronic Coronary Insufficiency and Severe Left Ventricular Dysfunction; Annals of Noninvasive Electrocardiology; Online Version of Record published before inclusion in an issue - Afanasiev S. A.; Pavlyukova E. N.; Kuzmichkina M. A.; Rebrova T. Yu.; Anfinogenova Ya. J. Yana Jonovna; Likhomanov K. S.; Karpov R. S. (2016, 2016)
Title screen